The Formalization of Sharia in Aceh to Discipline the Female Body - Zuly Qodir; Hasse Jubba; Mega Hidayati; Dyah Mutiarin (Al-Jami'ah: Journal of Islamic Studies, 2022)
The formalization of sharia (particularly regional regulations on sharia in Aceh) since 2001 up to 2019 had incorporated economic and political contents between local and national elites. Such condition was a result of local and national elite interests gaining political advantages wherein sharia was utilized as a tool by the elites to dominate civilians. Due to political interests, civilians became marginalized by sharia. The current article demonstrates that local and national political elites had used sharia for their political interests without considering the substantial purpose of sharia itself. Women, in particular, are disadvantaged by the various regulations (qanun) issued by wilayatul khisbah as the guardians of sharia in Aceh. The article also aims to show existing contradictions between the ideal aspirations of wilayatul khisbah and the actual practice of regional regulations pertaining to sharia on the ground, namely the involvement of political elites in advocating sharia, which has not made people become more religious but provoked them to resist in secret instead. Data in the article were acquired through literature study, field observations, and in-depth interviews with a number of informants[Formalisasi syariah Islam di Aceh melalui Peraturan Daerah (Qanun) sejak 2001 telah melibatkan kolaborasi ekonomi dan politik antara elit lokal dan nasional. Situasi tersebut menyebabkan kepentingan elit lokal dan nasional berebut keuntungan politis sebagai alat mendominasi warganya, sehingga menyebabkan kepentingan warga termarjinalisasi. Artikel ini membahas elit lokal dan nasional yang memanfaatkan syariat Islam untuk kepentingannya sendiri tanpa mempertimbangkan tujuan utamanya. Perempuan sering dirugikan oleh sejumlah aturan yang dikeluarkan oleh tim penegak syariat Islam (wilayatul khisbah). Artikel ini juga memperlihatkan kontradiksi antara  aspirasi ideal dan praktik di lapangan lembaga wilayatul khisbah yang mana keterlibatan elit politik dalam advokasi syariat Islam tidak mendorong lebih religius tetapi justru mendorong warga melawan diam-diam. Data artikel ini didapatkan dari studi literatur, observasi lapangan dan wawancara mendalam dengan sejumlah informan.]